2010
DOI: 10.3233/jad-2010-091150
|View full text |Cite
|
Sign up to set email alerts
|

The Amnestic Syndrome of Hippocampal type in Alzheimer's Disease: An MRI Study

Abstract: The Free and Cued Selective Reminding Test (FCSRT) is a verbal episodic memory test used to identify patients with mild Alzheimer's disease (AD). The present study investigates the relationships between performance on FCSRT and grey matter atrophy assessed with structural MRI in patients with AD. Three complementary MRI-based analyses (VBM analysis, ROI-based analysis, and three-dimensional hippocampal surface-based shape analysis) were performed in 35 patients with AD to analyze correlations between regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
92
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 50 publications
14
92
1
3
Order By: Relevance
“…Nevertheless, clinical pathological studies suggested that NINCDS-ADRDA criteria are reliable for the diagnosis of AD [62]. Finally, even if most of AD patients included in our study are at the mild stage of AD, several subjects present with moderate AD and were severely impaired in the FCSRT, in line with previous studies with AD [19,63,64]. Indeed, a floor effect in some patients is also reported in previous studies and does not affect the VBM analysis.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Nevertheless, clinical pathological studies suggested that NINCDS-ADRDA criteria are reliable for the diagnosis of AD [62]. Finally, even if most of AD patients included in our study are at the mild stage of AD, several subjects present with moderate AD and were severely impaired in the FCSRT, in line with previous studies with AD [19,63,64]. Indeed, a floor effect in some patients is also reported in previous studies and does not affect the VBM analysis.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, involvement of the hippocampus is a hallmark feature of AD and is considered to underlie the predominant amnesic syndrome [49]. Furthermore, previous studies reported correlation between scores of FCSRT free recall and atrophy in the left hippocampus and parahippocampus in AD and MCI subjects [19,20,22]. This finding is concordant with a recent study reporting that either the Rey Complex Figure delayed recall and the FCSRT delayed Recall, visual and a verbal episodic memory tests, are associated with total hippocampal volume in cognitively normal older adults [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the available neuropsychological data on the ROS cohort (Supplemental Table 1), we focused on the relationship of neuronal insulin signaling and regulating molecules in CA1 to episodic memory, given the close association of CA1 atrophy in AD to this type of memory (72). Linear regression analyses revealed that, apart from Akt 2, basal activation states of insulin signaling and regulating molecules in CA1 were highly related to episodic memory ( Table 7).…”
Section: Neuronal Irs-1 Ps 616 and Irs-1 Ps 636/639 Are Negatively Comentioning
confidence: 99%
“…Both these brain areas express the IR and IGF-1R (64,65), as well as insulin-sensitive GLUT4 (66)(67)(68)(69)(70). We then focused on the HF to study the causes and consequences of brain insulin resistance, since it is more directly involved in AD pathogenesis (61,63) and cognitive decline (71,72).…”
Section: Introductionmentioning
confidence: 99%